Promotion Language And Destination Image Sustainability: Implications For Socio-Economic Development In Tangerang City - Hayati, Asfitri; Basit, Abdul; Lolita, Lulu Ayu (LPPM Universitas PGRI Sumatera Barat, 2025)
This study aims to analyze the influence of language in digital promotions on the image of tourist destinations by highlighting four key indicators: message clarity, narrative appeal, language style, and cultural appropriateness. Destination image is measured through two main dimensions: cognitive perception, which relates to tourists' knowledge and rational understanding of the destination, and affective perception, which reflects the emotional bond and aesthetic impression formed. This study used a quantitative survey approach, collecting data from 110 respondents, residents of Tangerang City, using a purposive sampling technique. The results indicate that message clarity, narrative appeal, language style, and cultural appropriateness contribute significantly to shaping tourists' cognitive and affective perceptions. Among these variables, message clarity and narrative appeal proved more dominant in strengthening audiences' rational understanding of the destination, while language style and cultural appropriateness played a more significant role in building emotional closeness and trust in local values. These findings confirm that an effective digital promotion strategy relies not only on delivering factual information but also on packaging the message in a way that aligns with the cultural characteristics and linguistic preferences of the target audience. Theoretically, this research expands the study of tourism marketing communications by emphasizing the importance of linguistic and cultural dimensions in influencing destination image formation. Practically, the research findings provide strategic implications for tourism stakeholders in designing more persuasive digital promotional content, oriented toward local values, and supporting the sustainability of culture-based tourism. Thus, this research makes a significant contribution in bridging communication theory, destination branding strategies, and digital marketing practices rooted in local cultural wisdom.